RNA silencing-mediated resistance to a crinivirus (Closteroviridae) in cultivated sweetpotato (Ipomoea batatas L.) and development of sweetpotato virus disease following co-infection with a potyvirus - Kreuze, Jan F.; Klein, I.S.; Ghislain, M.; Valkonen, J.P.T.; Untiveros, M.; Cuéllar, Wilmer Jose; Lajo, G.; Cipriani, P. (Wiley, 2008)
Sweetpotato chlorotic stunt virus (SPCSV; genus Crinivirus, family Closteroviridae) is one of the most important pathogens of sweetpotato (Ipomoea batatas L.). It can reduce yields by 50% by itself and cause various synergistic disease complexes when co-infecting with other viruses, including sweetpotato feathery mottle virus (SPFMV; genus Potyvirus, family Potyviridae). Because no sources of true resistance to SPCSV are available in sweetpotato germplasm, a pathogen-derived transgenic resistance strategy was tested as an alternative solution in this study. A Peruvian sweetpotato landrace 'Huachano' was transformed with an intronspliced hairpin construct targeting the replicase encoding sequences of SPCSV and SPFMV using an improved genetic transformation procedure with reproducible efficiency. Twentyeight independent transgenic events were obtained in three transformation experiments using a highly virulent Agrobacterium tumefaciens strain and regeneration through embryogenesis. Molecular analysis indicated that all regenerants were transgenic, with 1–7 transgene loci. Accumulation of transgene-specific siRNA was detected in most of them. None of the transgenic events was immune to SPCSV, but ten of the 20 tested transgenic events exhibited mild or no symptoms following infection, and accumulation of SPCSV was significantly reduced. There are few previous reports of RNA silencing-mediated transgenic resistance to viruses of Closteroviridae in cultivated plants. However, the high levels of resistance to accumulation of SPCSV could not prevent development of synergistic sweet potato virus disease in those transgenic plants also infected with SPFMV.